Genotype and mutation patterns of macrolide resistance genes of Mycoplasma pneumoniae from children with pneumonia in Qingdao, China, in 2019. (December 2021) - Jiang, Fa-Chun; Wang, Rui-Fang; Chen, Ping; Dong, Li-Yan; Wang, Xia; Song, Qin; Wan, Yi-Qiu; Song, Qin-Qin; Song, Juan; Wang, Yan-Hai; Xia, Zhi-Qiang; Xia, Dong; et al.
Highlights: Rate of Mycoplasma pneumoniae (MP) infection in children with pneumonia in Qingdao in 2019 was high (59.0%). Of 46 MP samples, 57.1% were classified as type 1 and 42.9% as type 2. Macrolide resistance mutation A2063G in domain V of 23S rRNA were identified in all sequenced MP. ABSTRACT: Objectives: This study assessed the incidence and resistance of Mycoplasma pneumoniae (MP) in children in Qingdao, China, in 2019. Methods: We detected MP infection in 78 pharyngeal swabs from children with pneumonia by qPCR. The RepMP4 element in the P1 adhesin gene, domain V of the 23S rRNA gene, and the L4/L22 ribosomal proteins were amplified by nested PCR. Evolutionary analysis was conducted based on the P1 gene sequence. Resistance mutations in domain V of the 23S rRNA gene and L4/L22 ribosomal proteins were analysed. Results: The incidence of MP infection in children with pneumonia was 59.0% (46/78). The mean duration of MP infection was longer than that of non-MP infection. According to P1 gene sequencing of 21 samples, 12 (57.1%) were type 1 and 9 (42.9%) were type 2. Drug resistance mutations A2063G in domain V of 23S rRNA gene and T508C in L22 were identified from all sequenced MP. However, mutations at positions 2064 and 2617 were not found in this study. C162A mutation appeared in most type 2 samples. A430G mutation appeared in one type 1 sample and in several type 2 samples. T279C mutation in L22 was mostly found in type 2 samples. Conclusion: The incidence of MP infection was 59.0% in children with pneumonia in Qingdao in 2019. Type 1 MP infection was slightly more common than type 2, indicating that the genotype of MP is gradually shifting from type 1 to type 2. Macrolide resistance mutation A2063G could be detected in all sequenced MP.